Characteristics of physiology, phenology, and drought susceptibility index of two varieties of Job’s tears under water deficit stress - Wicaksono, Fiky Yulianto; Sinniah, Uma Rani; Ruminta; Sumadi; Tati Nurmala (Universitas Sebelas Maret, Surakarta, 2022)
Job’s tears or hanjeli (Coix lacryma-jobi L.) is a functional food crop with less popularly cultivated and longer life cycle than paddy and maize, so that it is potentially exposed to drought stress in the dry season in tropical areas. This study aims to evaluate the physiology, phenology, and drought susceptibility index lack of both Job’s tears varieties under water deficit stress. The study was conducted in quantitative method, by using 2 populations of ma-yuen and stenocarpa varieties which were treated with two levels of watering treatment during the vegetative phase (6 to 12 weeks after sowing), i.e. every day watering and every three days watering. Observations were made on physiological traits, phenology, and drought susceptibility index. The results showed that water deficit decreased stomatal conductance and chlorophyll content, but it could increase electrolyte leakage and proline content. Increasing proline content had a significant correlation with crop yields improvement. Flowering time was prolonged as the effect of drought stress in both varieties. Based on drought susceptibility index, stenocarpa was more tolerant than ma-yuen. However, some farmers might still cultivate the ma-yuen due to the soft seed shell character, therefore, this study finding could be used as a basis for developing further plant irrigation techniques for sensitive variety amid a prolonged dry season.